2017
DOI: 10.1016/j.polymer.2016.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of nanostructured films with an ultralow volume fraction of hard phase

Abstract: We demonstrate in this paper how polymerization induced self-assembly (PISA) using RAFT can be used to synthesize very asymmetric but monodisperse poly(acrylic acid)-b-poly(nbutyl acrylate) block copolymers, PAA-b-PBA, with a short PAA block and a long PBA block. In the course of the surfactant-free emulsion polymerization, core-shell particles form in water, with the short hydrophilic block located at the water-particle interface, and the long hydrophobic block constituting the particle core. Drying at room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 30 publications
1
27
0
4
Order By: Relevance
“…11 In particular, we reported recently how one can take advantage of the current developments in polymerization-induced self-assembly (PISA) to prepare nanostructured latex-based films combining high stiffness and high deformability, seemingly contradictory properties. 12,13 The materials were exclusively made of spherical soft-core/hard-shell particles, constituted of highly asymmetric poly(acrylic acid)-b-poly(n-butyl acrylate), PAA-b-PBA, block copolymers, synthesized in water thanks to a RAFT emulsion polymerization process. 14 The enhanced stiffness of the materials at low strain was attributed to the percolating network formed by the glassy PAA shells.…”
mentioning
confidence: 99%
“…11 In particular, we reported recently how one can take advantage of the current developments in polymerization-induced self-assembly (PISA) to prepare nanostructured latex-based films combining high stiffness and high deformability, seemingly contradictory properties. 12,13 The materials were exclusively made of spherical soft-core/hard-shell particles, constituted of highly asymmetric poly(acrylic acid)-b-poly(n-butyl acrylate), PAA-b-PBA, block copolymers, synthesized in water thanks to a RAFT emulsion polymerization process. 14 The enhanced stiffness of the materials at low strain was attributed to the percolating network formed by the glassy PAA shells.…”
mentioning
confidence: 99%
“…More recently, Chenal et al. interestingly showed that poly(acrylic acid)‐ b ‐poly( n ‐butyl acrylate) (PAA‐ b ‐P n BA) synthesized by emulsion PISA produced homogeneous and cohesive transparent polymer films . The percolating network of the thin high glass transition temperature ( T g ) layer at low volume fraction was at the origin of these remarkable mechanical properties of the low T g polymer film.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Singlet oxygen, a powerful oxidant produced by energy transfer from the photoactivated sensitizer to (PAA-b-PnBA) synthesized by emulsion PISA produced homogeneous and cohesive transparent polymer films. [24,25] The percolating network of the thin high glass transition temperature (T g ) layer at low volume fraction was at the origin of these remarkable mechanical properties of the low T g polymer film. Another study showed that the adsorption of PAA-b-PnBA diblock copolymer onto soft acrylic latex particles prior to their film formation also creates a percolating network that raises the elastic modulus, creep resistance, and tensile strength of the final film.…”
Section: Emulsion Polymerizationmentioning
confidence: 99%
“…Both the size and shape of nanoparticles are crucial factors that impact their properties and applications. [15][16][17][18][19] For instance, the size and shape of PISA nanoparticles have been found to significantly affect their in vivo biodistribution. [20] Although many applications have been proposed for PISA nano-objects including lubricants, pigment encapsulation, catalysis systems, coatings, and Pickering emulsifiers, their use in biomedical science is arguably the most exciting.…”
Section: Doi: 101002/marc201800438mentioning
confidence: 99%
“…Both the size and shape of nanoparticles are crucial factors that impact their properties and applications . For instance, the size and shape of PISA nanoparticles have been found to significantly affect their in vivo biodistribution .…”
Section: Introductionmentioning
confidence: 99%